2021
DOI: 10.1002/app.50530
|View full text |Cite
|
Sign up to set email alerts
|

Proton exchange composite membranes comprisingSiO2, sulfonatedSiO2, and metal–organic frameworks loaded inSPEEKpolymer for fuel cell applications

Abstract: Proton exchange membrane fuel cell (PEMFC) is a promising technology that offers a clean and efficient renewable energy source. The hybrid SiO2, sulfonated SiO2 (SSiO2), and metal–organic framework‐5 (MOF‐5) incorporated sulfonated poly (ether ether ketone) (SPEEK) ternary composite membranes are fabricated using dry phase inversion technique for PEMFC. The membrane performance is evaluated in terms of water uptake, ion exchange capacity, methanol permeability, and proton conductivity (PC) measurements. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 60 publications
1
19
0
Order By: Relevance
“…Commercial Nafion‐117, a per‐fluorinated membrane has high stability in both oxidation and reduction environment and possess a considerable proton conductivity. Although it has several advantages, it faces several short comings: (i) high cost, (ii) loss in performance at high operating temperature, (iii) excessive swelling with water, (iv) loss in mechanical stability and (v) low proton conductivity [14–27] . Considering the drawbacks of the commercial membrane, this study focusses on the development of alternative electrolyte membrane that is of low cost, high proton conductivity, chemically and mechanically stable under fuel cell operating conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Commercial Nafion‐117, a per‐fluorinated membrane has high stability in both oxidation and reduction environment and possess a considerable proton conductivity. Although it has several advantages, it faces several short comings: (i) high cost, (ii) loss in performance at high operating temperature, (iii) excessive swelling with water, (iv) loss in mechanical stability and (v) low proton conductivity [14–27] . Considering the drawbacks of the commercial membrane, this study focusses on the development of alternative electrolyte membrane that is of low cost, high proton conductivity, chemically and mechanically stable under fuel cell operating conditions.…”
Section: Introductionmentioning
confidence: 99%
“…4 The mechanical stability of SPEEK ternary composite membrane doped with sulfonated SiO 2 and MOF-5 was improved, and the proton conductivity was 3.69 mS cm À1 , 32% higher than neat SPEEK membrane. 21 Another way of incorporating MOFs in membrane is blending into polymer matrix directly. For example, Huang et al 22 blended MOF-C-SO 3 H into SPEEK matrix, and the composite membrane showed higher proton conductivity and lower methanol permeability than that of Nafion 115.…”
Section: Introductionmentioning
confidence: 99%
“…Methanol penetration was inhibited and mechanical property of UiO-66-NH 2 @NFs/Nafion composite membrane was enhanced owing to the electrostatic interaction between the nanofiber framework and SO 3 H in the Nafion matrix. 7 Therefore, researches 3,4,7,[21][22][23] have confirmed that the introduction of MOFs into polymer matrix can enhance proton conductivity by forming acid-base pairs or constructing proton transport channels.…”
Section: Introductionmentioning
confidence: 99%
“…Composites are materials made from two or more distinct components with significantly different physical or chemical properties [ 1 , 2 ]. These materials have a wide range of applications, including in the aerospace, automotive, and construction industries [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%